Destination of Organic Waste Produced at Manaus Free Fairs - Santos, Amanda Vanessa Silva Dos; Lima, Alexandra Amaro de; Lima, Larissa Roberta Gomes de; Bezerra, Igor Felipe Oliveira (International Journal of Advanced Engineering Research and Science, 2019)
Free fairs have always been the target of many regulars, which leads to producing tons of organic waste, but do not always have an efficient destination mechanism for organic waste. A correct disposal of waste is of paramount importance, as it prevents them from going into the process of decomposition in inappropriate places. In this phase, the release of slurry occurs, liquid that can contaminate soil and groundwater. The work aimed to point out the visible problems caused by organic waste, map and make comparisons between the main free fairs of Manaus, besides promoting a correct destination for organic waste produced in them. It was possible to analyze that the healthiness of free fairs are going unnoticed, with this it is clear that the disposal of organic waste is not receiving due attention. Through the questionnaire applied to fairs, consumers and waste pickers, a negative result was obtained regarding the infrastructure of free fairs.